Financial Integration of the European Union Financial Markets. A PCA Approach - Stanciu Cristian Valeriu; Spulbar Andrei Cristian (Studies in Business and Economics)
European stock markets are a complex and dynamic terrain, requiring sophisticated methods of analysis to understand their degree of interconnectedness and integration. The paper investigates the financial integration of European Union (EU) financial markets using a dynamic Principal Component Analysis (PCA) approach. By calculating the Financial Integration Index (FII) from daily stock market index returns and volatilities, we provide a comprehensive analysis of the integration trends over the past two decades across three distinct groups: the EU-27, the Eurozone, and the Non-Eurozone emerging economies. Our findings indicate an increased evolution of financial integration for all groups, with the Eurozone and Non-Eurozone groups exhibiting higher levels of financial integration compared to the broader EU-27. The results highlight that major crises significantly influence the dynamics of financial integration. Finally, the study underscores the higher sensitivity of volatility-based FII compared to return-based FII, making it a more effective measure for real-time monitoring of financial market integration. Our findings have several important implications for policymakers, which should monitor volatility closely as an early warning indicator of financial distress, and for portfolio managers, which have to consider both returns and volatility when assessing international portfolio diversification strategies.